Bilateral fornix infarction presented with acute amnesia: case report. Issue 1 (2nd January 2022) - Zhang, Hui; Zhang, Ya; Jiang, Xin; Lv, Peiyuan; Dong, Yanhong
ABSTRACT: Acute episodes of amnestic syndrome can be a challenging diagnostic problem. Except for nonvascular etiology, thalamic strokes or infarction involving several temporal lobe structures has been reported in earlier cases. The authors report a patient who suddenly developed memory loss without any other focal neurologic deficits. Brain magnetic resonance imaging (MRI) with diffusion-weighted imaging (DWI) performed 1 day after onset revealed acute infarction involving the bilateral fornix column and the genu of corpus callosum. Because simple fornix infarcts often have no obvious positive neurological signs, most of the related manifestations were provided by family members, are easy to be diagnosed falsely, and missed in clinical areas, we suggest that bilateral fornix infarction should be considered in the diagnosis of an acute onset amnestic syndrome.